Estabelecimento do IHRF no âmbito SIRGAS: contextualização histórica e densificação - Inoue, Mariana Eiko Borba (2024)
This dissertation was carried out in two parts. The first part deals with the evolution and current situation of altimetric systems in South America, intending to contribute to the International Height Reference Frame (IHRF). A historical description of these systems is presented, highlighting mainly the efforts of Working Group-III “Datum Vertical”. Furthermore, tests were conducted involving the 17 stations established for the IHRF in South America, in relation to five global geopotential models (MGGs) to obtain normal altitudes. Then, the methodologies for obtaining the geopotential number were compared using the quasi-geoidal model QGEOID2023 and five MGGs. As a result, it was found that for normal altitudes the SGGUGM-2 presented the lowest standard deviation of ±8.19 cm, while the EGM2008 presented the highest standard deviation of ±17.02 cm. As for the second comparison, for IHRF stations, the methodology based on geoid models presents better performance. The second part of this dissertation deals with obtaining normal altitudes linked to the IHRF for 7 high points located in the southeast region. In this sense, the methodology for calculating normal altitudes was presented, as well as for calculating a quasi-geoidal model (QGEOIDE_MG2024) using the Least Squares Collocation (CMQ) technique. Regarding normal altitudes, comparisons were also made with values obtained from the QGEOID2023 and QuGe-MG models. These values were compared with the models provided by IBGE. The QuGe-MG and QGEOIDE_MG2024 models presented similar values in areas with gravimetric densification, but discrepant in places with limited densification. The QGEOID2023 model demonstrated the smallest differences, indicating that the Downward continuation technique had a distinct impact on the results.